2021
DOI: 10.1002/pd.5834
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis in fetuses with duodenal obstruction: It is not just trisomy 21

Abstract: Objective To explore the copy number variants (CNVs) in case of fetal duodenal obstruction (DO) and assess the associated prenatal findings and postnatal outcomes. Materials and methods This retrospective study reviewed 51 fetuses with DO and the findings of chromosomal microarray analysis (CMA) used as a first‐tier test in our institution between January 2014 and May 2019. Results The frequency of pathogenic aberrations in fetuses with DO was 15.7% (8/51), including 9.8% (5/51) pathogenic CNVs. Three fetuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
2
8
3
Order By: Relevance
“…The incremental diagnostic yield of CNV-seq in complicated CGIOs (20%) was higher than that in isolated CGIOs (4.8%), and the highest prevalence of pCNVs/likely pCNVs was found in the duodenal stenosis/atresia group (17.5%), followed by the anorectal malformation group (15.4%). These data were inconsistent with the reports by Bishop et al [ 13 ] in which a pathogenic microdeletion was found only in isolated duodenal atresia and by Zhang et al [ 15 ] in which no significant difference in pCNVs was observed between the isolated group and complicated group. However, we believe that the divergence might be due to the relatively low number of fetuses included in those studies.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…The incremental diagnostic yield of CNV-seq in complicated CGIOs (20%) was higher than that in isolated CGIOs (4.8%), and the highest prevalence of pCNVs/likely pCNVs was found in the duodenal stenosis/atresia group (17.5%), followed by the anorectal malformation group (15.4%). These data were inconsistent with the reports by Bishop et al [ 13 ] in which a pathogenic microdeletion was found only in isolated duodenal atresia and by Zhang et al [ 15 ] in which no significant difference in pCNVs was observed between the isolated group and complicated group. However, we believe that the divergence might be due to the relatively low number of fetuses included in those studies.…”
Section: Discussioncontrasting
confidence: 96%
“…The 13q deletion, resulting in Waardenburg syndrome type 4A (OMIM 277580), was the most frequently identified CNV in our study (cases 1 and 2). This finding was consistent with a finding in a previous study [ 15 ]. CNV-seq revealed a 9.76-MB deletion in 13q21.33q34 and an 8.99-MB deletion in 13q22.31q33.3.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations